Prevalence and Configurations of C-Shaped Canals in Permanent Mandibular Second Molars in a Saudi Arabian Population: A CBCT Study. - Alam, Fayyaz; Patil, Santosh R.; G., Maragathavalli; Al-Zoubi, Ibrahim A.; Gudipaneni, Ravi Kumar; Alam, Mohammad Khursheed (International Medical Journal, 2019)
Objective: To evaluate the prevalence and configurations of C-shaped canals in permanent mandibular second molars using cone-beam computed tomography (CBCT) Material and methods: CBCT images of 171 patients comprising 326 permanent mandibular second molars were evaluated for the presence of C-shaped root canals. Of the 171 CBCT images examined, 16 had a unilateral intact molar, and 155 had bilateral molars in which the distribution of unilateral and bilateral occurrences of C-shaped canals was analyzed respectively. Chi-square test was used to correlate the prevalence of the C-shaped canals with gender and age, and also to correlate the number of the canals with the direction of the root grooves. Results: A total of 12.57% of teeth and 18.71% of patients showed a C-shaped canal. No significant difference in the distribution between the gender and age groups was noted. Majority of the C- shaped molars had three (36.58%) followed by two (31.70%) canals, mainly with root grooves in a buccal direction (80.48%) in comparison to lingual (19.51%). Conclusion: The prevalence of C-shaped canals in the mandibular second molars was 12.57% with varying anatomical configuration, majority of these were having three and two canals and most of the teeth the C-shaped canals were grooved in the buccal direction.